Концепція державного суверенітету в контексті застосування кіберсили - Камінський, Ігор Іванович; Каминский, Игорь Иванович; Kaminskyi, Ihor I. (My University, 2017)
У статті досліджується питання здійснення державами своїх суверенних прав у кіберпросторі. Автор намагається встановити правову природу останнього, щоб з’ясувати, чи є можливість розглядати принцип невтручання, який тісно пов’язаний із концепцією державного суверенітету, як міжнародно-правову підставу заборони застосування кіберсили.

В статье исследуется вопрос осуществления государствами своих суверенных прав в киберпространстве. Автор пытается установить правовую природу последнего, чтобы выяснить, есть ли возможность рассматривать принцип невмешательства, который тесно связан с концепцией государственного суверенитета, как международно-правовое основание запрета применение киберсилы.

The paper explores the issues concerning execution by states of their sovereign rights within cyberspace. Recent years has shown vulnerability of all states to the cyber attacks. This put on an agenda the need for establishment of an ability of international law to respond to cyber attacks; within the prism of the concept of non-armed force the Author proposes to qualify such attacks as the use of cyberforce. Firstly, at the present stage of development of international law, a normative prohibition on the use of non-armed cyberforce is not established in Article 2(4) of the UN Charter. Given the nature of realization of non-armed measures by the states, the Author suggests the hypothesis that the international legal prohibition of the latter follows from another basic principle of international law – the principle of the prohibition of intervention in matters which are within the domestic jurisdiction of any state (the principle of non-interven- tion). Since it is closely linked to the concept of state sovereignty, there is an urgent necessary to establish the existence of sovereign rights in cyberspace. To this effect, the Author investigates the legal nature of cyberspace in order to find out whether it is possible to consider the principle of non-intervention as an international legal ground for the prohibition of the use of cyberforce. As a result, the Author points out that states can not exercise sovereignty over cyberspace as a virtual environment, because it is a legal fiction as an object of legal regulation. At the same time the Author proves that states have sovereign rights over their cyber infrastructure, as well as the responsibility to control this infrastructure and to prevent it from deliberate use in order to harm other states. Such conclusion gives reasons to suggest that state sovereignty refers to cyberspace, so the principle of non-intervention can be explored as a norm prohibiting the use of cyberforce.
Камінський І. І. Концепція державного суверенітету в контексті застосування кіберсили / І. І. Камінський // Альманах міжнародного права. – 2017. – Вип. 16. – С. 3-10.
Keywords: державний суверенітет; незбройна сила; застосування кіберсили; принцип невтручання; государственный суверенитет; невооруженная сила; применение киберсилы; принцип невмешательства; state sovereignty; non-armed force; use of cyberforce; principle of non-intervention